EU fiscal rules: Do they destabilize and inhibit economic activity? - György Kopits (EconPol Forum, 2023)
EU member states that have continuously complied with the Stability and Growth Pact's budget deficit reference value have experienced much lower volatility and higher growth rates than those which violated the reference value. Also, most complying member states recorded a pronounced decline in the public debt-to-GDP ratio in the subperiods before and after the EU debt crisis. Therefore, adherence to the reference values for the general government deficit and debt, as proposed by the European Commission for the reform of the EU fiscal framework, are compatible with the overarching stability, growth, and debt sustainability goals. Encouragement is warranted of growth-friendly structural reforms and of public investment in the member states' medium-term structural-fiscal plans while complying with the deficit and debt reference values, as envisaged by the European Commission. The proposed shift to the government net expenditure benchmark as the single operational rule, as long as it is consistent with convergence to the debt reference value, is an important step toward simplicity, transparency, and greater stability. Conversion of the Recovery and Resilience Facility into a permanent central stabilization mechanism should be considered for adoption in the new fiscal framework, to mitigate multi-country shocks and to strengthen stability and sustained growth within the Union
Keywords: 330